Investment decisions with two-factor uncertainty - Tine Compernolle; Kuno J. M. Huisman; Peter M. Kort; Maria Lavrutich; Cláudia Nunes; Jacco J. J. Thijssen (Journal of Risk and Financial Management, 2021)
This paper considers investment problems in real options with non-homogeneous two-factor uncertainty. We derive some analytical properties of the resulting optimal stopping problem and present a finite difference algorithm to approximate the firm's value function and optimal exercise boundary. An important message in our paper is that the frequently applied quasi-analytical approach underestimates the impact of uncertainty. This is caused by the fact that the quasi-analytical solution does not satisfy the partial differential equation that governs the value function. As a result, the quasi-analytical approach may wrongly advise to invest in a substantial part of the state space.
Keywords: 330; investment analysis; optimal stopping time problem; two-factor uncertainty